Inferior Vena Cava Filters: An Overview - Paul Haddad; Jasmine Peng; Madeline Drake; Maham Rahimi (Methodist DeBakey Cardiovascular Journal)
For patients with existing venous thromboembolisms (VTEs), anticoagulation remains the standard of care recommended across multiple professional organizations. However, for patients who developed a deep venous thrombosis (DVT) and/or a pulmonary embolism and cannot tolerate anticoagulation, inferior vena cava (IVC) filters must be considered among other alternative treatments. Although placement of a filter is considered a low-risk intervention, there are important factors and techniques that surgeons and interventionalists should be aware of and prepared to discuss. This overview covers the basics regarding the history of filters, indications for placement, associated risks, and techniques for difficult removal.